KAMPUS MENGAJAR DI SDN 006/IV JAMBI MENINGKATKAN LITERASI DIGITAL, PENDIDIKAN KARAKTER, DAN KESEJAHTERAAN SISWA MELALUI INOVASI PEMBELAJARAN - Arini Syafitri (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
The Teaching Campus at SDN 006/IV Jambi is an initiative that has successfully integrated learning and community service to improve digital literacy, character education and student welfare. By promoting the use of literacy pages, reading aloud activities, and 5S culture, this program creates a holistic learning environment. Efficient library administration, promotion of dental and oral health, installation of anti-bullying banners, and literacy and numeracy festivals demonstrate a comprehensive approach to educational development. This entire effort was carried out through collaboration between field supervisors, the Teaching Campus team, and the school, providing a positive impact on student character, increasing literacy, and developing relevant skills. The Teaching Campus at SDN 006/IV Jambi has succeeded in achieving its goal as an agent of change in education and community services